(untitled) (Third Sector Social Economic Review, 2024)
According to the convergence hypothesis, which is a inference of the neoclassical growth approach, poor countries with a lower per capita income will catch up the rich countries with a higher per capita income after a certain period of time. In order to investigate this inference, the validity of the convergence hypothesis in N-11 countries was tested in the study. In this context, stationarity analysis was performed using annual data for the period of 1960-2021. Within the scope of analysis, firstly, the cross-sectional dependence between countries was investigated and the presence of cross-sectional dependence was determined. Then, Bahmani-Oskooee et al. (2014) panel Fourier unit root test used to examine stationarity. The Fourier test results showed that the series were stationary at level values in Nigeria, Pakistan, and the Philippines. Therefore, it has been revealed that the incomes of these countries converge to the incomes of high-income countries, but the convergence hypothesis is not valid in other countries.